At the edge of time : exploring the mysteries of our universe's first seconds - Hooper, Dan, 1976- (Science essentials (National Academy of Sciences (U.S.)), 2019)
"Scientists in the past few decades have made crucial discoveries about how our cosmos evolved over the past 13.8 billion years. But there remains a critical gap in our knowledge: we still know very little about what happened in the first seconds after the Big Bang. At the Edge of Time focuses on what we have recently learned and are still striving to understand about this most essential and mysterious period of time at the beginning of cosmic history. Taking readers into the remarkable world of cosmology, Dan Hooper describes many of the extraordinary and perplexing questions that scientists are asking about the origin and nature of our world. Hooper examines how we are using the Large Hadron Collider and other experiments to re-create the conditions of the Big Bang and test promising theories for how and why our universe came to contain so much matter and so little antimatter. We may be poised to finally discover how dark matter was formed during our universe's first moments, and, with new telescopes, we are also lifting the veil on the era of cosmic inflation, which led to the creation of our world as we know it. Wrestling with the mysteries surrounding the initial moments that followed the Big Bang, At the Edge of Time presents an accessible investigation of our universe and its origin."--Provided by publisher